Fog-Cloud: Efficient Task Scheduling Mechanism for Load Balancing Technique Using KHA – Task Scheduling Algorithm - R., Archana; Mohan Kumar, K. Pradeep (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Fog-Cloud is a computing paradigm. It can able to process, manage and Storage the data virtually. This enhances cloud computing by decentralizing its capabilities to the fog nodes. These fog nodes, positioned near the network's edge, the diverse storage capacity, computation, and processing capabilities. They can analyze requirements and respond to emergencies, processing and executing tasks. The restricted computational power of fog nodes presents a significant challenge in efficiently scheduling tasks among different fog nodes within their deadlines, while minimizing delays, costs, and energy consumption. Task Scheduling is the more crucial issue in fog computing. An Effective Task Scheduling Mechanism will improve the efficiency and Quality of the Service (QoS) in the computing Paradigm. The resource in the Fog Computing is lesser when compare to the Cloud. So it’s necessary to enhance the performance of the task scheduler. The proposed the dynamical scheduling task method for dynamically pairing tasks with resources comprises three essential components: a recourse availability check, and a priority method. The batch system effectively utilizes resource capacity and priority methods to match tasks with fog nodes. A notable benefit of this approach is the reduction of the search space achieved through batch processing. This technique has been executed using iFogSim and cloudlet for generating the workload with the current state-of-the-art. The comparative assessment involved various quality parameters, including delay, execution time, energy consumption, etc., revealing an average enhancement of 37.3%.